ADAPTABILITY OF E-TRAINING IN INDIA FOR EMPLOYMENT (International Journal of Food and Nutritional Sciences, 2022)
With the way work is changing quickly and the way people live becoming more digital, it is very easy as well as more effective to train the people using E-platform systems. This training can cover things like technologies, products, services, culture, and policies, among other things. Because of how quickly things are changing, organisations need to keep learning to stay competitive and keep their employees up to date on day-to-day changes. E-learning is a great way to do thisWith the rapid development of digital technology and the establishment of virtual learning institutions that offering online courses including online degrees to students, that's why E-education is becoming increasingly popular. E-Learning will play an important role in the future as a tool for teaching in the classroom and as a platform for self-study to improve skills. The major goal of this research is to find the important parts of e-learning for developing skills that are needed on the job. Universities and colleges have looked for the best ways to train their employees on the job. E-training led to better results, especially when more learning resources were made available and when the training course had some hybrid parts. Due to the growth of globalisation, many firms have begun to rely on e-training because it can reach huge groups of individuals in many districts or countries, reduce expenses, and disseminate essential knowledge. The goal of this study is to find out how well technology-based e-training in India can help people get jobs. Find out how e-training helps business school students get jobs. The results revealed that E-training is really helpful to students to learn new things and get better at what they already know because it gives them up-to-date information. Also, everyone who filled out the survey agreed that E-training is far better than the traditional system of training as well as it costs less for the B-Schools.